Application of single cell multiomics points to changes in chromatin accessibility near calcitonin receptor like receptor and a possible role for adrenomedullin in the post-shock lung - Armstead, Brandon E.; Lee, Chung Sunny; Chen, Yaping; Zhao, Runping; Chung, Chun-Shiang; Fredericks, Alger M.; Monaghan, Sean F.; Ayala, Alfred (Frontiers in Medicine, 2023)
INTRODUCTION: Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) is a commonly occurring sequelae of traumatic injury resulting from indirect insults like hypovolemic shock and/or extrapulmonary sepsis. The high lethality rate associated with these pathologies outlines the importance of clarifying the ‘priming’ effects seen in the post-shock lung microenvironment, which are understood to bring about a dysregulated or overt immune response when triggered by a secondary systemic infectious/septic challenge culminating in ALI. In this pilot project, we test the hypothesis that application of a single cell multiomics approach can elucidate novel phenotype specific pathways potentially contributing to shock-induced ALI/ARDS. METHODS: Hypovolemic shock was induced in C57BL/6 (wild-type), PD-1, PD-L1 or VISTA gene deficient male mice, 8-12 weeks old. Wild-type sham surgeries function as negative controls. 24-hours post-shock rodents were sacrificed, their lungs harvested and sectioned, with pools prepared from 2 mice per background, and flash frozen on liquid nitrogen. N=2 biological replicates (representing 4 mice total) were achieved for all treatment groups across genetic backgrounds. Samples were received by the Boas Center for Genomics and Human Genetics, where single cell multiomics libraries were prepared for RNA/ATAC sequencing. The analysis pipeline Cell Ranger ARC was implemented to attain feature linkage assessments across genes of interest. RESULTS: Sham (pre-shock) results suggest high chromatin accessibility around calcitonin receptor like receptor (CALCRL) across cellular phenotypes with 17 and 18 feature links, exhibiting positive correlation with gene expression between biological replicates. Similarity between both sample chromatin profiles/linkage arcs is evident. Post-shock wild-type accessibility is starkly reduced across replicates where the number of feature links drops to 1 and 3, again presenting similar replicate profiles. Samples from shocked gene deficient backgrounds displayed high accessibility and similar profiles to the pre-shock lung microenvironment. CONCLUSION: High pre-shock availability of DNA segments and their positive correlation with CALCRL gene expression suggests an apparent regulatory capacity on transcription. Post-shock gene deficient chromatin profiles presented similar results to pre-shock wild-type samples, suggesting an influence on CALCRL accessibility. Key changes illustrated in the pre-ALI context of shock may allow for additional resolution of ‘priming’ and ‘cellular pre-activation/pre-disposition’ processes within the lung microenvironment.